Navigating Barriers: Access to Justice and Legal Protection for Rohingya Refugees in Bangladesh - Badsha Mia; Joynab Binta Mariam Kali; Faijul Islam (PT Mattawang Mediatama Solution, 2026)
The Rohingya refugee crisis is an immense humanitarian challenge in South Asia. More than one million Rohingya individuals from Myanmar currently reside in refugee camps in Cox’s Bazar, Bangladesh, due to persecution and violence in their native country. Despite Bangladesh's considerable humanitarian gesture in offering sanctuary, the lack of a legal refugee protection system has impeded the Rohingyas' ability to seek justice. Protection of justice for these stateless Rohingya refugees entails many legal, institutional, and socio-political barriers. Ensuring access to justice for these stateless Rohingya refugees requires navigating complex legal, institutional, and socio-political barriers. This study examines the justice-seeking processes available to Rohingya refugees in Bangladesh, identifies the principal barriers to accessing these mechanisms, and evaluates the effectiveness of existing legal and policy frameworks. The study used a mixed-method approach, integrating qualitative interviews, focus group discussions (FGDs), and legal content analysis, revealing that structural discrimination, absence of legal identity, inadequate institutional capacity, and restrictive national laws substantially impede access to justice. The findings reaffirm the pressing need for policy reforms, legal empowerment efforts, and enhanced institutional collaboration across state agencies, NGOs, and other international organizations. The study suggests policy recommendations to incorporate access to justice into a comprehensive framework of human rights and sustainable solutions for the Rohingya refugee crisis in Bangladesh.